Calcium coordination polymer containing dimethylphosphate ligands and exhibiting nucleating properties towards α and Β crystal polymorphs of isotactic polypropylene - Maciej Dębowski; Mateusz Kullas; Krystyna Czaja; Beata Sacher-Majewska; Marcin Bączek; Maciej Dranka; Andrzej Ostrowski; Zbigniew Florjańczyk (Scientific Reports)
Abstract The synthesis, structure and thermal properties of a one-dimensional coordination polymer based on calcium bis(dimethylphosphate) (CaDMP) are reported. The rod-like particles of CaDMP crystallized from water in a monoclinic space group P21/c, and contained Ca[O2P(OCH3)2]2 polymeric chains consisting of the octahedrally coordinated Ca2+ ions bridged by the tridentate dimethylphosphate ligands. The variable temperature powder X-ray diffraction measurements showed that this structure undergoes anisotropic thermal expansion upon heating, with no polymorphic transitions occurring up to 190 °C. Thermolysis of CaDMP began around 260 °C leading to the formation of calcium condensed phosphates and volatile oxophosphorus species. A detailed differential scanning calorimetry (DSC) analysis, combined with a fitting of the experimental data to the Avrami or Liu–Mo kinetic models, revealed that CaDMP accelerates isothermal and non-isothermal crystallization of isotactic polypropylene (iPP). DSC and wide-angle X-ray scattering measurements confirmed the presence of α-iPP and β-iPP crystal domains in the systems loaded with CaDMP particles. The crystallographic analysis indicated that β-iPP polymorph formed via epitaxial crystallization on the surface of CaDMP crystals. Mechanical tests proved that the CaDMP-containing composites exhibited better ductility and impact strength than neat iPP.